1987
DOI: 10.1007/bf00265667
|View full text |Cite
|
Sign up to set email alerts
|

The significance of age on symptoms and urodynamic- and cystoscopic findings in benign prostatic hypertrophy

Abstract: To evaluate influence of age on symptomatology and objective parameters in benign prostatic hypertrophy, preoperative findings in 199 unselected patients during one year were analysed. Symptoms of bladder instability increased with age, as did incidence of uninhibited detrusor contractions and bladder trabeculation, whereas maximum urine flow and obstructive complaints decreased, although prostatic size was the same. In the oldest age groups only was increasing prostatic size associated with increasing bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 5 publications
0
12
1
1
Order By: Relevance
“…Mean ( SD , range) total PSA and free PSA levels were 2.18 (1.76, 0.08-5.15) and 0.07 (0.54, 0.026-1.30) ng/mL, respectively. The IPSS was 15.67 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean ( SD , range) total PSA and free PSA levels were 2.18 (1.76, 0.08-5.15) and 0.07 (0.54, 0.026-1.30) ng/mL, respectively. The IPSS was 15.67 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)). …”
Section: Resultsmentioning
confidence: 99%
“…Nocturia was once regarded as an irritative or filling symptom, and closely associated with BPH and BOO [8,9]. However, various medical or surgical therapies for BPH or BOO do not improve nocturia [10].…”
Section: Discussionmentioning
confidence: 99%
“…This would result in an additional 9% of patients who were excluded from surgery because their pathologic Qmax is based on a decompensated or weak detrusor muscle and not on BPH, and reduces the failure rate based on global subjective assessment of outcome to 8.3%. max* Simonsen et al [10] found a correlation max* Until prospective randomized trials can be estab lished, the value of pressure-flow studies in correctly pre dicting patients with a successful versus an unsuccessful outcome should probably best be reserved for patients with an equivocal Qmax or those patients in whom the results of symptom score assessment and flow rate mea surements are discrepant. Furthermore, the urodynamic community's responsibility is to establish intra-individ ual values, to decrease examiner variability of the test and to establish guidelines as to the proper conduct of these studies.…”
Section: Documentation Of Subvesical Obstructionmentioning
confidence: 99%
“…An evaluation such as this could simply con sist of a digital rectal examination (anatomical hyperpla sia), flow rate measurement and PVR measurement (subvesical outlet obstruction), and the administration of a Response Criteria 10 Roehrborn…”
Section: Correlation Between Response Criteriamentioning
confidence: 99%
See 1 more Smart Citation